Scattering and bound states of fermions in the modified Hulthen potential - Castro, A. S. de [UNESP]; Armat, A.; Hassanabadi, H. (Springer, 2014)
In the present work the scattering of a fermion in the modified Hulthen potential is considered with a general vector and scalar and we solved the Dirac equation in the one-dimensional space. The transmission and reflection coefficients are reported. The bound-state solution is also given. The study shows the asymptotic behavior of the wave function in bound-state and scattering states solutions.